Policy lessons of the development experience - Hughes, Helen (New York : Group of Thirty, 1985)
As countries overcome their human-resource constraints they can adopt policies that will replicate the East and Southeast Asian high growth experience
Bibliography: p. 23-24.
osc 20/08/2021
Loans
Keywords: Economic development